2005
DOI: 10.1088/0026-1394/43/1/010
|View full text |Cite
|
Sign up to set email alerts
|

Features of Co/C and Ni/C eutectic transitions for use in thermocouple thermometry

Abstract: Eutectic cells of Co/C and Ni/C for use in thermocouple calibration were manufactured and tested to investigate their melting and freezing characteristics using type B thermocouples. It was observed that the melting and freezing behaviour of Co/C and Ni/C systems are very similar. The freezing plateaus were found to be flatter than those of melting, but the melting points were closer to the ideal transition temperatures, which is an extrapolated value to zero temperature difference from the set temperature to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 8 publications
1
27
0
Order By: Relevance
“…Novel high-temperature fixed points based on metalcarbon eutectic alloys [1][2][3] have been shown to be high-performance temperature standards above the freezing point of Ag (962 • C), and their use could certainly reduce the scale-realization uncertainties [4] and address practical thermometry needs [5][6][7][8][9][10]. A good overview of the current state of research with respect to high-temperature fixed points (HTFP) can be found in [11].…”
Section: Introductionmentioning
confidence: 99%
“…Novel high-temperature fixed points based on metalcarbon eutectic alloys [1][2][3] have been shown to be high-performance temperature standards above the freezing point of Ag (962 • C), and their use could certainly reduce the scale-realization uncertainties [4] and address practical thermometry needs [5][6][7][8][9][10]. A good overview of the current state of research with respect to high-temperature fixed points (HTFP) can be found in [11].…”
Section: Introductionmentioning
confidence: 99%
“…especially of thermocouples, was recognized [5][6][7][8]. The actual calibration uncertainty of thermocouples at temperatures higher than the freezing point of copper (1,084.62 • C) rises from about ±0.3 K at 1,100 • C to about ±1.5 K at 1,550 • C [9], due to the absence of reliable high-temperature fixed points in this temperature range.…”
mentioning
confidence: 99%
“…After evacuating the tube to 1.3 Pa, pure argon (99.999 %) with a volume fraction of 0.5 % hydrogen was admitted to the cell. The internal pressure was kept slightly higher than an ambient level [2,4].…”
Section: Methodsmentioning
confidence: 99%
“…These points can be used to calibrate thermometers or to check the linearity of a radiation thermometer. Particularly Fe-C, Co-C, Pd-C, and Pt-C eutectic points have been widely investigated for the calibration of thermocouples [1][2][3][4][5][6]. In addition, international comparisons of the M-C points by using thermocouples as transfer artifacts are in progress at EUROMET and the APMP [7].…”
Section: Introductionmentioning
confidence: 99%